The explicit portrayal of obscenity in television series towards the current trend of viewing patterns: a content analysis on Grey's Anatomy / Mohd Shahnawi Muhmad Pirus - Muhmad Pirus, Mohd Shahnawi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The portrayal of obscenity in television series is not a new issue in our society. It is a reasonable fact to be understood that the exposure to such explicit content of obscenity is acceptable in Western culture but somehow or rather, the acceptance of obscenity among the Asian society is still taboo and this has geared parents to pay greater attention to what type of media content should be watched by their children. The researcher believes the audience could also educate themselves by watching such television series since Malaysia is lacking in sexual education. This research consists of qualitative content analysis. The researcher had included the obscene visuals and dialogues in order to justify the existence of such sexual portrayal on the Grey’s Anatomy TV series. A theory was selected for this study— the application on selected variables from a previous research done by the Henry J. Kaiser Family Foundation (Sex on TV4, 2005). The researchers had found that such TV content could be a medium to promote safe sex messages since Malaysia lacks in sex education. The implication on theory was to distinguish the obscenity portrayal in TV series in shaping the audiences’ acceptance.